ESTROUS BEHAVIOUR, PHYSIO-CHEMICAL PROPERTIES AND VAGINAL CYTOLOGY OF CERVICAL MUCUS IN BEETAL GOATS DURING INDUCED ESTRUS - DOGRA, P; .DHALIWAL, G S; KASWAN, S (The Indian Journal of Animal Reproduction, 2016)
Sixty post-partum anestrus beetal goats were randomly divided into three groups of 20 each to compare the efficacy of norgestomet with or without prostaglandin (PGF2α) or eCG or both for the induction of estrus. Each goat subcutaneously received half norgestomet implant (1.5 mg) for 11 days either with eCG 500 IU on day 9 (Gp Norg+eCG), with PGF2α 50 µg on day 10 (Gp Norg+PG) or with both eCG and PG on day 9 and 10 of protocol, respectively (Gp Norg+eCG+PG). Subsequent to implant removal, estrus was detected twice a day using aproned buck and animals in estrus were mated twice at 12 h interval. The animals in estrus showed bleating, wagging of tail and standing heat. The cervical mucus discharge during induced estrus was more copious in goats that became pregnant, while it was scanty in their counterparts failing to conceive (p<0.05). The cervical mucus during induced estrus was clear with high degree of arborization and spinnbarkeit in majority of the goats. The pH of cervical mucus during induced estrus was 6.8 - 7.0 with dominance of superficia